Effect of nutrition education on the knowledge scores of urban households with home gardens in Morogoro, Tanzania. Issue 1 (December 2016) - Pillai, Aarati; Kinabo, Joyce; Krawinkel, Michael
Abstract Background Home gardens are an old agricultural practice playing a key role in household food security and diversity. Proximity of gardens to the home facilitates easy access to food and reduces household expenditure. Home gardens combined with nutrition education could improve household diets both quantitatively and qualitatively. The objective of this study was to assess the effect of a nutrition education intervention on families with home gardens in Morogoro, Tanzania. Methods Two cross-sectional nutrition surveys were conducted at different time points, the baseline in October–November 2013 and endline in May–June 2014. Between the surveys, an intervention consisting of three interactive nutrition education sessions was conducted in December 2013. The study targeted forty households owning home gardens in urban areas of Morogoro municipality. Mixed methods were used to collect data, including semi-structured questionnaires for quantitative data and focus group discussions for qualitative data. Results The estimated marginal means showed small statistically non-significant improvements in knowledge scores for vitamin A (p  = 0.145, partialη 2  = 0.065) and iron (p  = 0.403, partialη 2  = 0.022). There were more positive scores observed for both nutrients at endline compared with baseline. Composite knowledge scores calculated for participants showed improvements in the category with scores between 3 and 6 points, for both nutrients. Conclusion While a statistically significant improvement in knowledge scores was not observed, an increase in number of positive scores and composite knowledge scores indicate an improvement in nutrition knowledge among participants. These results show that families having home gardens and who are provided with nutrition education can improve the quality of their household diets. Nutrition education in combination with other agricultural interventions could be a potential tool to improve nutritional status and should be integrated into public health programmes and strategies.